Ninth Five Year Plan 1997-2002 and Annual Plan-1997-98 Draft Proposals Volume II Part-X-E Social Services Government of Meghalaya - Planning Commission (Planning Commission, 1997)
The Information Services has assumed greater importance with the increased developmental activities of the state. Adequate publicity to various developmental programme of the State government is given more thrust with the role objective of educating the people and enthuse in them a spirit of participation and involvement in the successful implementation of these Programme through the various media.
Planning Department